Application of Reciproval Teaching Model to Improve Student Learning Activities - Putri, Dewi Yulia; Rahmanelli, Rahmanelli (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
The purpose of this research is to perform direct the phenomenon from learned material of geography, so student activity increased in following learned process. Method of research that used in action research is descriptive method, which drawing activities and range in cycle. Cycle research of researching that has done achieved a remained target, unachieved a target at first cycle and second cycle. New target of research achieved at third cycle, whereas student activity in learned process increased further than before.